Comparison of different protocols & strategies for range queries in mobile Ad hoc networks - Rahman, Kazi Anisur; Hussain, Fuad; Das, Nilotpal (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2002.